Effectiveness of HEPA Filters in Reducing Airborne Bacteria in Public Health Laboratory Rooms in Bontang City, Indonesia - Sya’adah, Nurul Laili; Dwiyanti, Ratih Dewi; Nurlailah, Nurlailah (Baiman Bauntung Batuah Center, 2025)
Air is a basic human need whose quality needs to be maintained, especially in closed environments such as laboratories. Several factors, such as temperature, humidity, lighting, occupancy density, and ventilation systems, affect the presence of microorganisms in the room. Laboratory users can control microorganisms that cause air contamination by using High Efficiency Particulate Air (HEPA) filters. This study aims to determine the effect of HEPA filter use on the number of airborne germs in laboratory rooms. This type of research is an analytical observational study with a cross-sectional design, with nine rooms as research objects. Air samples were taken six times in each room, namely twice before the use of the HEPA filter (0 hour), twice after the use of the HEPA filter for 3 hours without activity, and twice after the use of the HEPA filter for 3 hours with laboratory service activities. Statistical tests used one-way ANOVA to analyze the data. The results showed that the average number of airborne germs before the use of the HEPA filter was 357,667 CFU/m³. After 3 hours of use of the HEPA filter without activity, the number decreased to 177,444 CFU/m³. After 3 hours of active HEPA filter use, the number of airborne bacteria decreased to 124 CFU/m³. The statistical test results showed a significance value of 0.000 (p < 0.05), which means there was a significant difference between groups. The conclusion is that the use of HEPA filters has a substantial effect on reducing the number of airborne bacteria in the Bontang City Health Laboratory room. Future researchers are advised to increase the duration of HEPA filter use and identify the types of bacteria in the laboratory room.